ORGANOGENESIS TANAMAN BAWANG MERAH (ALLIUM ASCALONICUM L.) LOKAL PALU SECARA IN VITRO PADA MEDIUM MS DENGAN PENAMBAHAN IAA DAN BAP - Rufaida, Anna; Waeniaty, Waeniaty; Muslimin, Muslimin; Suwastika, I Nengah (Univ. Tadulako, 2013)
Research on plant organogenesis Shallots (Allium ascalonicum L.) local Palu on MS medium with the addition of IAA and BAP, have been carried out in March and July 2013 in the Tissue Culture Laboratory, Faculty of Forestry Tadulako University. This study aims to get a combination of the concentration of IAA and BAP in MS medium onion plant organogenesis spur. Explants were used in the form of lateral shoots from the onion bulbs. This experiment is based on a complete randomized design (CRD) with 4 treatments, each treatment was repeated 5 times and every single unit test using a 2 explants. Growth media as treatments tested were: A1 (MS0 + 0.01 ppm IAA + 1 ppm BAP), A2 (MS0 + 0.05 ppm IAA + 1 ppm BAP), A3 (MS0 + 0.1 ppm IAA + 1 ppm BAP), A4 (MS0 + 0.5 ppm IAA + 1 ppm BAP). Judging from the appearance of the root, plantlet height, number of leaves, number of shoots, number of roots, chlorophyll content and the number of stomata per explant cultures tested The results showed that all treatments tested were able to induce organ onion crop Local Palu.. Based on these parameters, A1 is the best media in promoting organogenesis Local onion Palu. The media gives the best results appear to speed root, shoot number, leaf number and chlorophyll content. Other than that, the media A4 is also the best medium for the initiation stage plantlets before acclimatization. The media gives the best results for the number of stomata, while emerging roots and number of roots.